Principios generales del derecho y el derecho islámico - Pereda, Azul (2020)
There are jurists that sustain that the general principles of law, sources of International Law, are those that are recognized in all legal systems, determined by the comparative law method. Nevertheless, some authors and jurisprudence have shown that in practice the judges apply the law that they know, and that most of the members of the International Court of Justice have an education in the occidental legal system. This situation has caused some States, including Islamic States, not to feel represented by International Law. There is a tendency between States with a majoritarian Muslim population to establish Islamic Constitutions, but also to play a more important role in the international field and to settle international relations with non-Muslim States. These actors have manifested themselves against the lack of legitimation of International Law, which constitutes a problem because international conflicts among and with these States should be resolved according to the law. Consequently, it is really important the joint lecture of the article 38.1.c) and 9 of the Statute that establishes that the Court should be composed in a way that represents all nations, or at least the principal legal systems. The project's hypothesis is that the International Court of Justice doesn't take into account Islamic Law when it applies general principles of law and this situation has a correlation with the nationality and education of the judges